PENERAPAN HUKUMAN MATI TERHADAP PELAKU TINDAK PIDANA DITINJAU DARI HAK ASASI MANUSIA - Kiansantang, Ksatrio; Subroto, Mitro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Indonesia as a State of Law with Positive Law, namely the Criminal Code still imposes criminal sanctions in the form of the death penalty. In essence, the death penalty is a punishment by eliminating the life of the convict. However, the application of the death penalty caused a causa celebre (trigger) for the re-emergence of polemics against the pros and cons of the death penalty verdict. From a human rights perspective, death penalty sanctions do not conflict with national and international legal instruments, such as the 1945 Constitution, Law Number 39 of 1999 concerning Human Rights, the Universal Declaration on Human Rights 1948, and the International Covenant on Civil and Political Rights 1966. The methods used in this writing are juridical normative and descriptive-analytical. Keywords: Human Rights Perspective; Normative Juridical; Analytical Descriptive